Giving and Forgiving in Nietzsche and Derrida - Lemm, Vanessa (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This article makes a contribution to the current debate on forgiveness and gift-giving in contemporary political and social philosophy. This article presents Nietzsche’s conception of forgiveness as gift-giving beginning with Nietzsche’s critique of the Christian practice of forgiveness as an example of the spirit of revenge in order to then point out the affinities between the Nietzschean critique and what Derrida names ‘impure’ or ‘conditional’ forgiveness. It argues that overcoming revenge or ‘impure forgiveness’ requires an affirmation of the animality of the human being as a life force indispensable to the constitution of free and just forms of social and political life.